Ensino de astronomia: investigando a formação docente em um espaço não formal - Fontanella, Denise (2015)
Being a gift astronomy content as a structural theme in elementary school and to be part of our everyday research is justified to talk about teacher training for teaching astronomy in a non formal space. The research aimed to investigate the characteristics and implications of a course for teacher training related to Astronomy Teaching conducted by Polo Astronomical Casimiro Montenegro Filho. The study, qualitative, as north had a critical review of the literature in the area and the analysis of the speeches of the participants of the course teachers collected through questionnaires and interviews, as well as the analysis of the constitution of the course itself, these information collected through audiovisual recordings of classes. Data were analyzed based on the theory of Bardin content analysis (1977) and point out that when it comes to astronomy content teachers have many difficulties because they have initial or continuing education quality. Moreover, conceptual errors and misconceptions were detected in issues related to astronomy for us researchers and also by teachers during participation in the course. The data indicate difficulties in teacher education in relation to the area of Astronomy, however, point us suggestions to alleviate these difficulties, such as the course for teacher training in Astronomy, which proved to be an ally of the teacher to work contents, methodologies and potentially usable resources in the classroom to assist the teacher in the process of teaching and learning.